Atlas of the Qur'an - Shauqi abu khalil (Darussalam, 2003)
This atlas is new in its subjects, a subjects that has not been touched before. it helps whoever recites the Qur'an or studies it to specify the locations mentioned by the Noble Verses, and to mark those places of ancient people mentioned in the Qur'an.